Globalisasi dan Implikasinya bagi Inovasi Pendidikan Islam - Nurul Khotimah; Muslimah Muslimah (STKIP PGRI SITUBONDO, 2023)
This article examines the implications of globalization on Islamic education. Data collection methods used through the study of literature. Data is obtained through literature in the form of books, journals and online sources. The analysis method used is descriptive analysis where this method is appropriate to observe the phenomenon that is happening. The results of the discussion show that Islamic Education has new challenges and opportunities in facing globalization. So that an effort is needed, including by improving the quality of educators, reforming the subject matter, the need for technology, internalizing religious values, and collaborating with the community. Some of these efforts need to be done in order to continue Islamic Education according to the times.